Do you "like" my photo? : facebook use and body dissatisfaction and self-esteem - PASAGUI, JOANNA MARIE (Archīum Ateneo, 2018)
The use of social networking sites such as Facebook is pervasive among women who are between 18-25 years old, or those referred to as emerging adults.This demographic is also reported to be highly prone to having negative evaluation towards their bodies, or body dissatisfaction. The study examined Filipino women's Facebook use in relation to the sites photo-related activities and how this use associated with body dissatisfaction and low self-esteem. Data was gathered from 100 emerging adults, 50 of whom were college students and 50 were working professionals through online and pen and paper surveys. Respondents accomplished a questionnaire containing measures about their Facebook use and photo-relatedactivities, body satisfaction, self-esteem, and social comparisons. Findings revealed that respondents sought different gratifications from Facebook, and as such, used the site differently. Results revealed that use of Facebooks photo-related activities and exposure to the images of others was not related with Filipino women emerging adults body dissatisfaction and low self-esteem. Instead, Filipino emerging adult womens body dissatisfaction and low self-esteem was associated with Facebook instigated social comparisons.